Effectiveness of social media tools in promoting information literacy: a case of the University of Cape Town Libraries - Hlemfu, Malixole (Department of Knowledge and Information Stewardship, 2025)
Information literacy is a critical skill that is required for students to complete their assessments and for problem solving. Academic libraries play a key role in fostering and advancing information literacy. Since the outbreak of COVID-19, social media has emerged as a crucial alternative for engaging with students. This study investigates the effectiveness of the University of Cape Town Libraries' use of social media tools for promoting information literacy. Using a constructivism worldview and a case study research design, the study aimed to address four critical research questions: (1) what are the information literacy needs of University of Cape Town Humanities undergraduate students? (2) what social media tools are available at University of Cape Town Libraries for the promotion of information literacy to Humanities undergraduate students? (3) what challenges, if any, do Humanities undergraduate students face with engaging in University of Cape Town Libraries' social media tools? (4) what best practices may be put in place to ensure the effectiveness of social media tools to promote information literacy? Data was collected through online surveys from 100 randomly selected students and semi-structured interviews with six librarians. The findings revealed that while the majority of students are active on social media and engage with the libraries' social media tools, particularly Instagram, they primarily engage with the library when needing information about library resources during. This highlights the critical role of information literacy in maximising the use of available resources. Notably, the study identified significant barriers, including connectivity issues and limited access to devices, which impede the promotion of information literacy. Although University of Cape Town Libraries are addressing these challenges to some extent, the study underscores the need for more sophisticated strategies to address these challenges. Recommendations include diversifying social media engagement approaches, prioritising accessibility, fostering collaborative partnerships, and developing proactive communication strategies. Furthermore, the study points to the limited use of quantitative metrics for evaluating social media effectiveness, with only two librarians are actively monitor the social media tools. The study advocates for the creation of more engaging content and the implementation of rigorous assessment measures to enhance the effectiveness of social media tools in promoting information literacy